The language barrier : the overlooked challenge to equitable health care - Hussey, Nadia (South African Health Review, 2012)
This chapter examines the effects of language barriers on the access of patients and communities to quality health care. It also looks at communication challenges experienced by health professionals that provide this care. Using a case study of a rural hospital, the chapter highlights some of the challenges posed by the language barrier and explores current methods that English-speaking health professionals at this hospital use to overcome these difficulties. The case study findings indicate that the language barrier decreases work efficiency and the provision of holistic treatment. It makes communication time consuming, which increases frustration levels and decreases empathy, approachability and confidentiality. Current methods for overcoming problems include the use of untrained and ineffective interpreters - usually overworked nurses; linguistic codeswitching; and the use of a selection of key isiXhosa vocabulary. These methods have many drawbacks and are not suitable or sustainable. Recommendations for improving communication include the promotion of a culture of multilingualism, which includes language education as a part of professional development and the employment of trained interpreters. For multilingualism to occur, more research needs to be conducted, and the political will to address this problem must be demonstrated. Overcoming the language barrier needs to be prioritised and commitment must be made to implementing strategies that provide a multilingual patient base with a multilingual healthcare service.

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.